Technology integration in instructional delivery of college faculty: basis for a balanced scorecard - Jacob, Joseph M. (Parañaque City: Olivarez College, 2016)
This study attempted to assess the technology integration in instructional delivery of college faculty with an end view of developing an intended scorecard. Specifically, it sought to provide answers to the following research questions: 1. What is the profile of the respondents in terms of: 1.1. gender; 1.2. age; 1.3. course area; 1.4. academic qualifications; and, 1.5. teaching experience? 2. What are the current practices and the extent of technology integration in instructional delivery of the respondents? 3. How confident are the faculty-respondents in integrating technology in instructional delivery? 4. Is there a significant relationship among the respondents' confidence level, current practices, extent of integration, and technology integration barriers in their instructional delivery? 5. Is there a significant difference on the factors affecting technology integration in instructional delivery of respondents when grouped accordingly? 6. What technology barriers have placed great impact on instructional delivery of the respondents? 7. Based on the result of the study, what appropriate balance score card can be developed? Methodology This study utilized descriptive correlation method using statistical survey questionnaire by Gorder (2008) on Technology Integration Standards Configuration Matrix (TISCM) among eighty five (85) respondents who were general education and professional education faculty from Southville International School and Colleges, South SEED- LPDH College and SEED Academy, respectively. Frequency count and percentages were used to describe the profile of the respondents; while weighted means for the responses in survey questionnaire; and t-test, Pearson r, and ANOVA were utilized for the purpose of testing the hypotheses stated in this study.
Master Thesis
Keywords: Technology integration